Design of a VHF log-periodic dipole antenna - Ng, Xianyang (2015)
Very High Frequency (VHF) is widely used in our life, be it for broadcasting radio, television, two way radio system used for communication in military usage and even air traffic control. VHF frequency span from 30 MHz to 300MHz. In the lower frequency range, the length of the element can be humongous, up to 5m long for a half-wave dipole. Therefore, it is significant to look into reducing the size of the antenna. In this project, the standard log periodic dipole array (LPDA) antenna will be looked into to understand its operation principle and theory behind it. After which miniaturization technology will be discussed and the means to go about integrating the technique to the LPDA. After all the theory and analyses, the High Frequency Structure Simulator (HFSS), a simulation software will be used to simulate both the original LPDA and also the LPDA with miniaturization technology employed. The new structure will go through a series of parametric study to get the optimal parameters. The final design of LPDA have a good VSWR, radiation pattern, also there is a significant decrease in size.